Photo-tautomerization of acetaldehyde to vinyl alcohol: a potential route to tropospheric acids. - Andrews, D; Heazlewood, B; Maccarone, A; Conroy, T; Payne, R; Jordan, M; Kable, S (2012)
Current atmospheric models underestimate the production of organic acids in the troposphere. We report a detailed kinetic model of the photochemistry of acetaldehyde (ethanal) under tropospheric conditions. The rate constants are benchmarked to collision-free experiments, where extensive photo-isomerization is observed upon irradiation with actinic ultraviolet radiation (310 to 330 nanometers). The model quantitatively reproduces the experiments and shows unequivocally that keto-enol photo-tautomerization, forming vinyl alcohol (ethenol), is the crucial first step. When collisions at atmospheric pressure are included, the model quantitatively reproduces previously reported quantum yields for photodissociation at all pressures and wavelengths. The model also predicts that 21 ± 4% of the initially excited acetaldehyde forms stable vinyl alcohol, a known precursor to organic acid formation, which may help to account for the production of organic acids in the troposphere.